PERENCANAAN KOMPOSISI CAMPURAN BETON MENGGUNAKAN AGREGAT 10/20 DAN 20/30 - Tilsa M Amahoru; Soumokil Hengki Johnny; Sulastri Kakaly (Journal Agregate, 2022)
"Concrete Mix Planning using Gradations Size 10/20 and 20/30 This thesis is under the guidance of Soumokil Hengki Johnny and Sulastri Kakaly.The purpose of this study was to produce a concrete mix composition with variations of coarse aggregate gradations of 10/20 and 20/30 and to produce compressive strength of concrete with variations of coarse aggregate gradations of 10/20 and 20/30.Various studies on concrete have been carried out by many experts both in terms of material, composition, additives, and others. In this study, the authors used aggregates of 10/20 mm and 20/30 mm. The results of the concrete compressive strength test conducted at the Ambon State Polytechnic Laboratory showed that the characteristic concrete compressive strength for concrete using 10/20 mm aggregate at ages 7,14 and 28 were 20, 48 MPa, 26,70 MPa, and 30 respectively. .10 MPa. Whereas concrete using 20/30 mm aggregate at ages 7, 14 and 28 days respectively was 20.66 MPa, 24.53 MPa, and 31.18 MPa. From the results of the compressive strength test, it was found that there was a decrease in the compressive strength of concrete using large-size aggregate at the age of 14 days for 20/30 aggregate. The larger aggregate size can affect the compressive strength of the concrete, the compressive strength of the concrete will decrease if the maximum size of the aggregate increases and will also increase the difficulty in the process.Keywords: Aggregate Variation Concrete 10/20 And 20/30, Material Characteristics, Mix Design.